(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Couple of pivotally important aspects of ‘ANCIENT INDIAN POLITY’ and ‘MODERN INDIAN Constitution-Oriented-Approaches To DEMOCRACY & SECULARISM’ immediately captivate our attention once we resort to the evolution of Ancient Indian Polity since Time immemorial. The chronological passages of history together with the evolution of Indian CONSTITUTION advocating the gregarious strength of DEMOCRACY; a timeless testimony to the Right to Equality, Justice, Liberty & Fraternity; amply prove the veracity of the statement. It’s no exaggeration to identify Modern Democracy & Secularism being a sustainable development right from the time of Vedas– the mother of ancient Scripture, Literature, Inscriptions, Royal Eulogies & Anthologies chiming with the chronological passages of Historical hallmarks. Craning back to Ancient India, we can discover at length, the spirit of an amicable fraternity with the celebration of a cohesive togetherness. A discovery of that heritage encompassing a journey through Veda; Epics, Mythologies and vast anthological volumes of scriptural literature; helps us discover the lineage of a sustained glory. Say for example, the ‘Shanti Parva’ in Mahabharata not only discusses the science of polity but also advocates its own theories regarding the origin of state and kingship; essential state prerogatives to be implemented by an emperor; duties of different officials; undeniable expediencies of revenue and tax collection. After Mahabharata, Arthasastra comes out to be more a manual cum textbook for the administrators than a mere theoretical directives on polity. It aimed to discuss the philosophy and fundamental principles of administration coupled with a neatly practicable political science. It is chiefly concerned with the practical problems of governance and its machinery; their functioning during peace and war both. The text discusses all the details with an exhaustiveness that hitherto remains incomparable except some possible exceptions of Sukraniti. Therefore, the rock solid pillars of Indian Constitution are but a sustainable development upon a firm and consolidated groundwork of ancient Political texts.